Навершя руків'я меча з Чорнівського городища першої половини ХІІІ ст. - Калініченко, Віталій; Пивоваров, Сергій (Чернівці, Видавничий дім "Букрек", 2014)
The authors introduced into scientific circulation quite rare for the region discovery, namely head bronze finial medieval sword hilt, which was discovered on the Chornivka hillfort first half o f XIII century in 2012. Argued that the head pommel sword has baltic origin. Detection allows us to trace and find more to explore militaiy affairs o f the local population, in particular to trace mutual troop Chornivka hillfort with adjacent territories of Russia and Europe in the XIII century. The purpose of this study is to put into circulation actually first discovery details o f the sword, which clearly can be attributed to XII - early XIII century from Siret territory to the Middle Dniester river interfluve, namely head pommel or handle of a medieval sword and a comprehensive review of the findings, it’s analysis, interpretation and implementation types. Consequently, the typology A. Kirpichnikova by their morphological features head pommel sword with Chornivka hillfort of the type I - swords with bronze cross bronze pommel with five or seven parts. The shape of the pommel blades o f this type are similar to swords such as K, S, and TI by typologically V. Kazakyavichusa Bronze swords of the given type, as indicated by A. Kirpichnikov with cast ornament with circles characteristic of romance art XII century. This type o f sword was the inscription on the blade. All findings of this type swords found in the settlements and burials of the XII-XIII century. As pointed out by the researcher, in addition to Rus, swords of this type are found in Latvia and in the Volzhska Bulgaria. Outside Europe, it has not come out. A. Kirpichnikov believes that this type of Eastern European origin was as blades and handle detail. However, in the archaeological literature has repeatedly put forward the idea of the Baltic, as well as the Curonian manufacturing of swords of this type. Special attention is given to the study of such swords paid V. Kazakyavichus, which distinguishes this type called TI curonian. The timing of swords type TI curonian, the researchers puts forward a hypothesis that most swords of this type may appear already in the XI century. They gradually begin to appear in the Ponemannya in Belorussia. In the ХII-ХІІІ century they apply to the lands o f western Rus. A narrow stratigraphic dating of the finds and the materials enclosed systems allow to date this type o f swords — end of XII — 50 years of XIII century. The reasons for the disappearance of swords of this type and their reduction in the above-mentioned period due to the displacement of romance swords are still not able to completely displace them from the territory of Rus. With regard to ethnicity, we believe that the head pommel hilt of the sword is the Baltic production, namely the curonian. Corns is people who lived in the V-XVI centuries in West Baltic, on the south-eastern coast of the Baltic Sea in Western Latvia and western Lithuania. In the XIII century. Corns constantly at war with the Livonian Order, participated in military campaigns and battles. Chief among these is the battle of Durbe in July 13, 1260. The battle between the forces of the Teutonic Order during the Livonian Master Burchard command Hornhauzena background and Marshal Henry of Prussia Bote. Allies were his cours as mercenaries. But how could such a rare find to get to Chornivka hillfort? We believe that in the Chornivka hillfort could be a small garrison o f soldiers Baltic origin. As you know, obviously in the Chornivka hillfort family lived prince Andrew Yaroslavovich — wife and two sons - Yuri and Michael, who were granted land and property for "kormlenyya ”. Maybe his family arrived and a small contingent of troops just to the north (Baltic origin), because, man, “Danylivna ” - daughter of Daniel Romanovich Galician Andrew Yaroslavovich pursued a very active military policy just to the north of contemporary Rus. That is, there may be certain mutual influence of the north and south of Russia. These are the types of arrowheads Baltic, battle ax and a number o f other findings. Perhaps pommel sword belonged to a noble retainer. But the question of interpretation and military - political history based on items identified in the arms Chornivka hillfort is somethingfor the future, so considering this memo promising for further research into the history of the region, its study will be continued with the new findings.
Head of the sword pommel from Chormvka hillfort first half of XIII century
Навершие рукояти меча с Черновского городища первой половины ХІІІ в.
Keywords: Галицько-Волинське князівство; Чорнівське городище; озброєння; меч; навершя; руків ’я; типологія